Reimagining Critical Race Theory in Education: Mental Health, Healing, and the Pathway to Liberatory Praxis - McGee, Ebony O.; Stovall, David (Educational theory, 2015)
Long‐standing theoretical education frameworks and methodologies have failed to provide space for the role mental health can play in mediating educational consequences. To illustrate the need for such space, Ebony McGee and David Stovall highlight the voices of black undergraduates they have served in the capacities of teacher, researcher, and mentor. Building from the theoretical contributions of intellectual giants like Frantz Fanon and W. E. B. Du Bois, the authors attempt to connect oppressive social systems to the psyche of the oppressed in a way that is relevant to black students. McGee and Stovall pose a challenge to the current research trend of attributing the survival of black students at traditionally white institutions primarily to grit, perseverance, and mental toughness, noting that research on the aforementioned qualities often fails to properly acknowledge multiple forms of suffering. Utilizing the lens of Critical Race Theory (CRT), the authors also challenge the construct of grit to consider the extent to which the mental health concerns of black students go undetected. Although critical race theorists have unmasked and attacked the racial trauma experienced at all levels of the educational system, the connection of CRT to mental health and wellness research is in its embryonic stages. For these reasons, McGee and Stovall argue that CRT scholars need to incorporate praxis to address mental health and wellness in order to address a fuller spectrum of black students' racialized worlds. Ultimately, they seek interdisciplinary perspectives that can help identify and foster strategies to support black students in the project and process of healing from multiple forms of racialized trauma they experience within and beyond their educational encounters.